Influence of Gas Bubbles on the Operation of a Centrifugal Pump - Ahmadov, A.S.; Dadash-zada, A.R. (Herald of Azerbaijan Engineering Academy, 2023)
Analysis shows that many liquids contain soluble gas in them. Such fluids have low viscosity and density. However, when pumping liquids, a number of problems arise, one of which is the appearance of bubbles in the mixture. Such liquids with gas do not obey the law of homogeneous liquid and gas. Therefore, in recent years, special attention has been paid to the hydromechanics of two-phase systems, such as oil-gas, water-steam, etc. the appearance of gas bubbles also affects the operation of centrifugal pumps, which manifests itself during pumping. The basic equations of a centrifugal pump are obtained taking into account the gas in the mixture.